2015
DOI: 10.17140/aftnsoj-1-119
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Supplementation Reduces Enteric Colonization of Campylobacter jejuni in Broiler Chickens and Down-Regulates Expression of Colonization Genes

Abstract: Campylobacter is one of the leading causes of foodborne bacterial gastroenteritis worldwide, and poultry is considered as the most common source of human infections. Campylobacter is prevalent in most poultry flocks and a reduction of Campylobacter in poultry would greatly reduce the risk of campylobacteriosis in humans. Unfortunately, efforts to reduce Campylobacter in pre-harvest poultry have been met with limited success. Preliminary studies with the natural compound, chitosan, demonstrate its ability to ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…counts in broiler chickens. In addition, RT-qPCR analysis revealed that chitosan down-regulated the expression of chicken colonisation genes when compared to a control (Arambel et al 2015). This suggested that chitosan supplementation could be a potential strategy to reduce the enteric colonisation of Campylobacter spp.…”
Section: Plant and Marine Extractsmentioning
confidence: 95%
“…counts in broiler chickens. In addition, RT-qPCR analysis revealed that chitosan down-regulated the expression of chicken colonisation genes when compared to a control (Arambel et al 2015). This suggested that chitosan supplementation could be a potential strategy to reduce the enteric colonisation of Campylobacter spp.…”
Section: Plant and Marine Extractsmentioning
confidence: 95%
“…Most commonly, Campylobacter has been linked to poultry products and linked to human cases of gastroenteritis in most cases as well as the Guillain-Barré syndrome, reactive arthritis, and irritable bowel syndrome or inflammatory bowel disease in the most severe cases [16,17]. Campylobacter is a major concern for infection in poultry production [16][17][18]. One route of contamination, also common to most other pathogens, is through livestock water sources [19].…”
Section: Campylobactermentioning
confidence: 99%
“…The use of prebiotics is most often seen coupled with a complementary probiotic (often described as "synbiotics"), and recent research has demonstrated the benefits that may exist with the coordinated use of such a complementary intervention. A list of the prebiotics identified for pathogen reduction in the literature is presented in As previously discussed, Campylobacter is among the leading foodborne pathogenic bacteria found in livestock and the majority of bacteria are introduced into the human food chain via poultry [16,17]. In an evaluation of Campylobacter colonization in hatchling chicks, chitosan (a compound from the chitinous shells of crabs and shrimp) was shown to reduce the population of C. jejuni both in vitro and in vivo when added to the feed [16].…”
Section: Prebioticsmentioning
confidence: 99%
See 2 more Smart Citations